2009
DOI: 10.1029/2008jd010602
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a mesospheric bore event observed with an all‐sky airglow imager at Tirunelveli (8.7°N)

Abstract: [1] A prominent front separating bright and dark regions of all-sky airglow images was recorded on the night of 22/23 March 2007, at the low-latitude Indian station Tirunelveli (8.7°N, 77.8°E) and is attributed to a mesospheric bore. With the help of complementary wind information from the colocated MF radar and temperature and density data from the SABER instrument onboard TIMED mission, the parameters of the bore are calculated and discussed. Because the observed wind at the emission altitude was orthogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 32 publications
5
42
0
Order By: Relevance
“…Thus, the bore cannot be filtered out. Similar results have been reported by other imager observations (e.g., Taylor et al, 1995;Smith et al, 2003;She et al, 2004;Narayanan et al, 2009;Bageston et al, 2011b). Bageston et al (2011b) found that small winds in the wave propagation direction do not have influence on the duct configuration, emphasizing the thermal duct.…”
Section: Propagation Environment Of the Bore Eventsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, the bore cannot be filtered out. Similar results have been reported by other imager observations (e.g., Taylor et al, 1995;Smith et al, 2003;She et al, 2004;Narayanan et al, 2009;Bageston et al, 2011b). Bageston et al (2011b) found that small winds in the wave propagation direction do not have influence on the duct configuration, emphasizing the thermal duct.…”
Section: Propagation Environment Of the Bore Eventsupporting
confidence: 80%
“…When only the OH emission observation is available, we are not able to discuss the complementary bore effect among different airglow layers. In contrast, bores with increased emission intensity behind the leading front have been reported by other observations Narayanan et al, 2009;Nielsen et al, 2006;Stockwell et al, 2006Stockwell et al, , 2011Fechine et al, 2009). In a recent paper, Bageston et al (2011a) reported a clear wave front followed by a series of wave crests.…”
Section: The Mesospheric Bore Eventmentioning
confidence: 46%
See 2 more Smart Citations
“…However, in regions having variable horizontal winds, it is often important to account for these influences [Simkhada et al, 2009]. This more complete version of the dispersion relation may be written as [Nappo, 2013] …”
Section: Gravity Wave Environment Calculationsmentioning
confidence: 99%